APOLOGIA STRATEGIES AND ETHICAL ASPECTS OF GOVERNMENT PUBLIC RELATIONS IN A CRISIS SITUATION - Kriyantono, Rachmat (representamen, 2019)
The research aims to evaluate apologia strategy based on ethical perspective of public relations. The research applies standards of ethics from The Indonesian Public Relations Association and Apologia Theory. Some research proves that the ability of an organization to deal with a crisis depends on the types of allegations during a crisis. The research tests whether the strategies of Government Public Relations (GPR) of Malang Regency also appropriate with these standard when the organization faces an allegation of corruption. Conducting content analysis on 47 editions of online news, the research reveals that the GPR has adopted ethical standard when delivery information in quote news as a channel of crisis communication. All the ethical standards applied are concerning to public interest, telling true information, address the economic, physical and psychological concerns of the public.Keywords: Apologia, Communication, Crisis, Ethics, Government Public Relations, Indonesia